Clinico- Pathological Study Of Ichthyosis Vulgaris - Nandy Utpal; Jayashree Nath Barbhuiya; Hazra B; Banerjee P P (Wolters Kluwer Medknow Publications, 1997)
A clinico- pathological study of 28 cases of ichthyosis vulgaris appeared with in the age of 5 years. The presence of the disease since birth was also found. While most (24) patients showed a diminution of severity in summer with an aggravation during winter, 4 patients followed the opposite seasonal pattern. Only in 4 patients, fine scales in the scalp were detected. One patient showed an affection of flexures. There was also a low occurrence of palmo- planter hyperkeratosis, follicular keratosis, fissuring of hands and feet and atopy.